Relationship between selected hormonal and metabolic parameters at birth and blood pressure during pre-adolescence (Colombia Medica, 2009)
Objective: The aim of the present study was to evaluate the relationship between selected hormonal parameters (at birth and at age 8 years) and blood pressure levels at pre-adolescence in a cohort of intrauterine growth retarded (IUGR) and normal birth weight infants (NBW). Methods: A cohort study from early pregnancy to childhood was performed. Seventy-six fetuses/children were evaluated between 1995 and 2004. Cord blood samples were taken at birth and several hormonal and metabolic parameters evaluated. Sixty-four children of the original cohort were available for blood sampling, blood pressure and anthropometric measures at a mean age of 8 years. 27 (42.2%) were IUGR and 37 (57.8%) were NBW. Multiple regression analyses were conducted with cord blood levels of hormonal and metabolic parameters at birth and at 8 years as independent variables and children’s blood pressure as dependent variable adjusted by IUGR status, gender, Body Mass Index and age of the child at the time of blood pressure evaluation. Results: The maternal age (26.6±5.8 vs 26.9±5.8 years old) and the gestational age at birth (39.1±1.4 vs 39.6±1.3 weeks) were similar between the groups. IUGR children were shorter (1.28± 0.09 m vs 1.33± 0.09 m, p=0.04). Growth hormone levels (GH) at birth were negatively associated with systolic blood pressure at 8 years of age (regression coefficients for umbilical cord blood levels: -0.9, 95% CI -2.03 to 0.04 mg/ml, p= 0.04). Conclusion: The alterations on blood pressure can begin in fetal life were levels of GH could have an important role.